The Rise of the Digital Therapist: Can AI-Powered Mental Health Therapy Offer a Viable Solution? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The global mental health crisis presents a formidable challenge, characterized by rising demand and significant barriers to access, including cost, stigma, a...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Clinical Decision Support